MEMBANGUN MASYARAKAT SEHAT DAN PEDULI KANKER MELALUI PENYULUHAN DAN PEMERIKSAAN KESEHATAN - Neni Legawinarni; Mawaddah; Putri Rahmadani (Jurnal Pengabdian Masyarakat, 2025)
Cancer is one of the leading causes of death that can be prevented through education and early detection. Low public awareness of risk factors, early signs, and the importance of health checks results in many cancer cases being discovered at an advanced stage. This community service activity aims to increase public understanding and conduct health checks related to cancer risk factors at the Bait Qur'an Mulia Foundation. The method used is an educational-participatory approach with a community-based empowerment strategy. The activity is carried out through preparation, implementation, and evaluation stages. The examinations include measuring blood pressure, body mass index, random blood sugar, and breast examinations for early cancer detection. The tools used include digital sphygmomanometers, scales and height meters, blood sugar monitors, and health education media. A total of 60 participants (45 women and 15 men) consists of members of the Bait Qur'an Mulia Foundation, including housewives, teenagers, the elderly and the general public. The examination results showed that 40% of participants had high blood pressure, 10% had a body mass index above normal, 20% had blood sugar levels above healthy limits, and none of the participants were found to have signs indicating breast cancer. The counseling provided successfully increased participant understanding, with 85% of participants able to re-explain the material. This activity demonstrates that integrated health education and screenings can be an effective strategy for raising awareness, encouraging preventative behaviors, and strengthening early cancer detection efforts in the community. It is recommended that similar programs be implemented on an ongoing basis to strengthen community self-reliance in maintaining health.